2023
DOI: 10.3389/fpubh.2023.1033532
|View full text |Cite|
|
Sign up to set email alerts
|

Digitizing tuberculosis treatment monitoring in Wuhan city, China, 2020–2021: Impact on medication adherence

Abstract: IntroductionDigital technologies can improve adherence to tuberculosis (TB) treatment. We studied the impact of digitizing TB treatment monitoring on adherence among TB patients in Wuhan, China, during 2020-2021.MethodsWe compared an electronic system introduced to monitor TB medication adherence (e-Patient Service System; e-PSS) with the p paper-based standard of care (TB Control Information System; TCIS) in terms of prescribed TB treatment doses taken by patients and patient outcome after six months of follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
0
5
1
1
Order By: Relevance
“…While one study[35] suggested that the technology was associated with an improvement in treatment adherence of persons with multi-drug resistant TB, the two other studies found conflicting results among persons with drug-sensitive TB. [36,37]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While one study[35] suggested that the technology was associated with an improvement in treatment adherence of persons with multi-drug resistant TB, the two other studies found conflicting results among persons with drug-sensitive TB. [36,37]…”
Section: Resultsmentioning
confidence: 99%
“…[19,20,29,48,52] Similarly, for interventions that involved smartphone technologies, most studies described various combinations of associated measures e.g., medication reminders, adverse event reporting, instant messaging, chat groups with providers and/or other patients. [37,53,54] The diversity of comparison strategies reported as the "standard of care" further complicates This substantially limits generalizability of findings regarding these two technologies to lowerincome country settings where TB burden is highest, yet where these technologies and the necessary technical and human resource infrastructure may be least accessible. Notably, however, our review does report robust findings from studies in LMICs: the DAT types implemented in these settings (e.g., SMS, 99DOTS, digital pillboxes) had variable or nonsignificant impacts on treatment outcomes, which has important policy implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The digital tool provided two options to patients—the reminder application or reminder smart pillbox—while one management application along with a management website were provided for medical staff to monitor patients’ medication adherence. A detailed description of tool utilization was introduced previously ( 17 , 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…Sembuh dari tuberkulosis juga membuat mereka lebih menghargai kesehatan dan nilai sumber daya alam yang mendukung kehidupan. Penelitian ini sesuai dengan penelitian yang menyatakan tipe pekerjaan seseorang juga memengaruhi penghasilan keluarga, yang pada gilirannya berdampak pada gaya hidup sehari-hari, termasuk pola makan yang sehat dan pemeliharaan kesehatan (Zhang et al, 2023). Sejalan dengan penelitian lainnya yang menyatakan potensi adanya faktor psikologis seperti kecenderungan alami untuk bersyukur atau sikap optimis seorang petani yang dapat membentuk pandangan positif terhadap hidup sehingga memiliki gratitude tinggi (Wnuk, 2020).…”
Section: Pembahasanunclassified